DAMPAK BEBAN KERJA SERVANT LEADERSHIP DAN KOMPENSASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PT. BAROKAH ADI SEJAHTERA MEDAN - Fuadi, Akmal; Handoko, Bagus; Nahrisah, Ezzah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze how the impact of Servant Leadership Workload and Compensation on increasing the work productivity of PT.Barokah Adi Sejahtera The population in this study was 150 people and all of them were sampled in this study using saturated sampling techniques. The analysis technique used is multiple linear regression. The results showed that workload had a positive and significant effect on employee work productivity. Servant leadership has a positive and significant effect on employee work productivity. Compensation has no effect on employee work productivity. Simultaneously, it shows that the impact of workload, servant leadership and compensation has a significant effect on the work productivity of employees of PT Barokah Adi Sejahtera